A different approach to treatment of failing Fontan: Transcatheter covered stent implantation - İlker Kemal Yücel; Şevket Ballı; Emine Hekim Yılmaz; Ahmet Çelebi (KARE Publishing, 2016)
A 5-year-old male with a double outlet right ventricle with noncommitted ventricular septal defect and pulmonary stenosis underwent a bidirectional Glenn operation at 2 years and a Fontan operation with ligation of the pulmonary trunk at 5 years. He presented with pleural effusion 3 months after the Fontan operation. Physical examination revealed a grade 3/6 systolic murmur in the pulmonary area. Echocardiographic evaluation revealed an antegrade pulmonary flow (APF) of gradient 80 mmHg across the ventriculopulmonary communication. Cardiac catheterization and angiography demonstrated the presence of residual antegrade pulmonary flow and stenosis at the pulmonary artery bifurcation. Both pathologies were treated using a single covered stent. Relief of the pulmonary artery stenosis and total occlusion of the residual APF was demonstrated on a control angiogram.